Prognostic relevance of CCAs/Ph− in CML settled: comment on Issa et al, page 2084 - Hehlmann, Rüdiger (Blood, 2017)
In this issue of "Blood", Issa et al. report that patients with chronic-phase chronic myeloid leukemia (CML) in remission after treatment with tyrosine kinase inhibitors (TKIs) with clonal chromosomal aberrations (CCAs) in Philadelphia chromosome-negative (Ph−) metaphases had a significantly worse survival than similar patients without CCAs. This study is notable for the large number of patients with CCAs (n=58) and the length of follow up (median, 7.6 years) (see figure).